Considerations on spatial crop load mapping. (19th December 2018) - Taylor, J.A.; Dresser, J.L.; Hickey, C.C.; Nuske, S.T.; Bates, T.R.
Abstract: Crop load, the ratio of vine size to mass of fruit harvested, is fundamental to viticulture. Measuring vine size and crop yield, the components of crop load, has historically been a labour intensive exercise that has limited the use of crop load information to improve management in vineyards. Recent advances in assessing vine vigour, size and yield using geo‐referenced sensors are starting to make high resolution crop load mapping possible. In this paper, the concept of crop load is revisited with an emphasis on how vine size and yield can be mapped in vineyards. Existing literature is reviewed on how vine size and yield vary spatially and temporally within vineyard blocks and the inference this has on the spatio‐temporal variability of crop load. An example of crop load mapping using sensor technology is presented to illustrate recent advances in sensor technology in viticulture. Finally, some emerging technology and knowledge gaps for implementing spatial crop load information into vineyard management are discussed.